Risk factors for catheter-related infections in patients on hemodialysis - Knežević Violeta; Đurđević-Mirković Tatjana; Božić Dušan; Stražmešter-Majstorović Gordana; Mitić Igor; Gvozdenović Ljiljana (Vojnosanitetski Pregled)
Background/Aim. Catheter-related infections are a significant morbidity and mortality cause in patients on hemodialysis. The objective of this study was to determine the incidence, to analyze risk factors and to identify etiological causes of catheter-related infections in these patients. Methods. The study was carried out at the Clinic for Nephrology and Clinical Immunology of the Clinical Centre of Vojvodina, from August, 2012 to May, 2015. One hundred and thirteen patients on chronic hemodialysis participated in the study. The risk factors of catheterrelated infections in the infected patients were to those in the control group, as follows: demographic and laboratory parameters, co-morbidities and the use of immunosuppressive therapy, the length of hemodialysis treatment, urgent catheter placement, the position and placement difficulties, the number of insertions and catheter maneuvering, the existence of permanent vascular access in maturation or without a vascular access in the course of catheter positioning, catheter life, surgical procedures (≤ 30 days from catheter placing), the length of hospitalization and isolated infection causes. Results. One hundred and ninety-seven catheters were placed in 113 patients, among which 182 of them temporary. The total number of catheter days was 17.842, the incidence of infections was 3.53/1,000 catheter days. During the monitoring period, 63 catheter-related infections were diagnosed, 54 (85.7%) with temporary and 9 (14.3%) with permanent catheters. Multivariate logistic regression analysis (with border values/ levels determined by receiver operating characteristic – ROC analysis) determined independent predictors of catheter-related infections in the following order: hemoglobin levels < 95 g/l (p < 0.001) and albumin levels < 33 g/l (p = 0.041), catheter duration of > 90 days (p = 0.004), > 2/day catheter maneuvering (p = 0.011) and the duration of hospitalization of > 15 days (p = 0.003). The main pathogen was Staphylococcus spp. Coagulase negative. Conclusion. Intensifying of prevention measures and infection control would significantly reduce the frequency of catheter-related infections and the number of hospitalizations. The timely creation of a native arteriovenous fistula would decrease the use of hemodialysis catheters.